2006
DOI: 10.1063/1.2206111
|View full text |Cite
|
Sign up to set email alerts
|

Tetrastack: Colloidal diamond-inspired structure with omnidirectional photonic band gap for low refractive index contrast

Abstract: vectors R 1 = a͑0,1/ ͱ 2,1/ ͱ 2͒, R 2 = a͑1/ ͱ 2,0,1/ ͱ 2͒ , R 3 = a͑1/ ͱ 2,1/ ͱ 2,0͒, and basis sphere positions, 0, 0.5R 1 , APPLIED PHYSICS LETTERS 88, 241920 ͑2006͒

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 25 publications
0
62
0
Order By: Relevance
“…Lifetime and relative contribution from slow and fast fl uorescence decay components calculated from a bi-exponential model. [ 53,54 ] The inherent photoluminescence of fullerene solvates also aligns with the desire for complex function from simple building blocks that has ignited experimental efforts in thin fi lm materials organized at the mesoscale. Notably, polarization independent pure 2D photonic band gaps (i.e., up to 10.6% gap-to-midgap ratio) have already been predicted for honeycomb lattices of hexagonal cross-section dielectric rods in air.…”
Section: Communicationmentioning
confidence: 88%
“…Lifetime and relative contribution from slow and fast fl uorescence decay components calculated from a bi-exponential model. [ 53,54 ] The inherent photoluminescence of fullerene solvates also aligns with the desire for complex function from simple building blocks that has ignited experimental efforts in thin fi lm materials organized at the mesoscale. Notably, polarization independent pure 2D photonic band gaps (i.e., up to 10.6% gap-to-midgap ratio) have already been predicted for honeycomb lattices of hexagonal cross-section dielectric rods in air.…”
Section: Communicationmentioning
confidence: 88%
“…This work on model anisotropic particles is particularly timely given the rapid recent advances in synthe- sizing anisotropic colloids, 14,15,16 and because one target for research in this field is to get particles with tetrahedral symmetry to assemble into a diamond-like crystal. 78 Our results indicate that the crystallization of such tetrahedral colloids might not be so straightforward, because of the potentially frustrating effects of the variety of local structures possible in the liquid phase. However, it is not clear how an additional potential term similar to that used by Zhang et al could be introduced into the intercolloidal potential to alleviate this.…”
Section: Three-dimensional Crystallizationmentioning
confidence: 91%
“…Moreover, it was demonstrated that two different structures can be self-assembled in one crystal structure from a binary colloidal dispersion [106,107]. These BCCs offer higher flexibility in engineering the photonic bandgap structures compared with one-size colloidal PCs, and these materials have found wide applications in sensing, protein patterning, and bioseparation [108,109].…”
Section: Aunps With Opalsmentioning
confidence: 99%